Programa De Vigilancia Epidemiológico En Salud Visual Para Los Trabajadores Del Molino Colombia S.A.S. En Venadillo Tolima 2017 (2017)
Rice is essential for food security, being the main product At a global level, after wheat, in Colombia there is a large production in some departments, one of them is Tolima, where the soils and climate They help its production, increasing its demand nationwide. The use of pesticides in rice crops draws attention due to its high exposure producing harmful effects on the health of workers